The Effectiveness of Online Learning: A comparative Study Focusing on Students’ Level of Performance in Reading Comprehension at Sabah University - M.Abdalla, Aumhani Ali; Deen Aljheme, Ebriek (Aljameai, 2023)
Abstract The current technological era has witnessed a great advancement in the world of online teaching and learning, and consequently merged in the educational procedures as methods or means of teaching. Online teaching and learning, for example, has become a common method that is used equivalently or sometimes alternatively to face-to-face teaching and learning methods. Moreover, the issue of using modern communication technologies for teaching and learning is a very important procedure used by many educational institutions. The purpose of this study is to compare the level of learners’ performance in reading comprehension of an online course to that of traditional procedure in reading course. This study is analytical in nature and the findings were obtained from a descriptive analysis. Questionnaires, and observations were used to specify the level of performance of both groups (traditional and online) and the differences between them. The course was designed for undergraduate students at English Language Department, Sabah University. The questionnaire was administered to 30 Libyan undergraduate students to measure their aspects of online and face-to-face learning. The results reveal that using online learning in teaching Libyan students was effective to a great extent, and there were no statistically significant differences could be credited to the traditional learning. The findings also demonstrate that Libyan students had a positive attitude towards online learning. لقد شهد العصر التكنولوجي الحالي تقدما كبيرا في عالم التعليم والتعلم عبر الإنترنت، وبالتالي تم دمجه في الإجراءات التعليمية كطرق أو وسائل للتدريس. وبدلك أصبح التدريس والتعلم عبر الإنترنت علي سبيل المتال طريقة شائعة يتم استخدامها بشكل مكافئ، و أحيانا بشكل بديل لأساليب التدريس والتعلم وجها لوجه. علاوة علي دلك فان مسألة استخدام تقنيات الاتصال الحديثة في التدريس والتعلم هي إجراء مهم للغاية تستخدمه كثير من المؤسسات التعليمية. الهدف من هده الدراسة هو مقارنة مستوي اْداء الطلبة في مادة استيعاب القراءة عبر الإنترنت بمستوي الإجراء التقليدي في المادة. فقد تم تصميم الدراسة لطلاب قسم اللغة الإنجليزية بجامعة سبها. فكانت هده الدراسة دراسة تحليلية في طبيعتها، وتم الحصول علي النتائج من التحليل الوصفي عن طريق استخدام الاستبانات والمشاهدة لتحديد مستوي أداء المجموعتين(التقليدية والإنترنت) والفرق بينهما لقد تم اجراء .الاستبيان الدي يحتوي علي تلاتون طالبا جامعيا ليبيا لقياس جوانب التعلم عبر الانترنت والتعليم وجها لوجه. اكدت النتائج ان التعليم عبر الانترنت كان في تدريس الطلاب الليبين كان فعالا الي حد كبير. ولم تكن هناك فروق دات دلالة احصائية بينهما. اضهرت النتائج ايضا ان الطلاب الليببين لديهم موقف ايجابي تجاه التعلم عبر الانترنت.